56.4k views
3 votes
0=x^(2)+2x-3 Solve using Quadratic Formula

User Charito
by
4.4k points

2 Answers

6 votes

Answer:


x=1,\\x=-3

Explanation:

The quadratic formula is given by
x=(-b\pm√(b^2-4ac))/(2a), where
x represents both real and nonreal solutions to a quadratic in standard form
ax^2+bx+c.

Thus, with the given quadratic
x^2+2x-3, we can assign values:


  • a=1

  • b=2

  • c=-3

Substituting in these values to the quadratic formula, we have:


x=(-2\pm√(2^2-4(1)(-3)))/(2(1)), \\\\x=(-2\pm√(16))/(2),\\\\x=(-2\pm 4)/(2),\\\\\begin{cases}x=(-2+4)/(2),x=(2)/(2)=\boxed{1}\\x=(-2-4)/(2),x=(-6)/(2)=\boxed{-3}\end{cases}

Verify by factoring:


x^2+2x-3=0,\\(x+3)(x-1)=0,\\\begin{cases}x+3=0,x=\boxed{-3}\:\checkmark\\x-1=0,x=\boxed{1}\:\checkmark\end{cases}

User Cllpse
by
5.1k points
1 vote

Answer:

Explanation:

x^2 + 2x - 3 =0

x^2 + 3x - x -3 = 0

(x) x (x+3) - (x + 3) = 0

(x+3) x (x-1) = 0

x+3=0

x-1=0

x=-3

x=3

x1 =-3, x2 = 1

User Phu
by
5.0k points